1978
DOI: 10.1128/aem.36.5.715-719.1978
|View full text |Cite
|
Sign up to set email alerts
|

Dry-heat destruction of lipopolysaccharide: mathematical approach to process evaluation

Abstract: A mathematical model was developed to estimate the number of logarithmic cycles (LDec) of lipopolysaccharide concentration destroyed by a dry-heat sterilization process. The LDec values calculated from the mathematical model agreed well with those obtained from the destruction of lipopolysaccharide by a dry-heat treatment. A discussion of how the mathematical model may be used to evaluate a dry-heat sterilization cycle is presented. This mathematical model and the dryheat destruction curves indicated existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 8 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…Similarly, studies by Tsuji et al suggested that increasing exposure time to compensate for lower processing temperatures would not suffice to ensure comparable LPS inactivation. 20 Later work by Ludwig and Avis 16,17 interpreted LPS inactivation to be biphasic, wherein endotoxin reduction was assessed using two temperature-dependent linear fits. Between 170 C and 250 C, calculated D values have been reported from 0.15 min to 3.4 h 16,[18][19][20] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, studies by Tsuji et al suggested that increasing exposure time to compensate for lower processing temperatures would not suffice to ensure comparable LPS inactivation. 20 Later work by Ludwig and Avis 16,17 interpreted LPS inactivation to be biphasic, wherein endotoxin reduction was assessed using two temperature-dependent linear fits. Between 170 C and 250 C, calculated D values have been reported from 0.15 min to 3.4 h 16,[18][19][20] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…20 Later work by Ludwig and Avis 16,17 interpreted LPS inactivation to be biphasic, wherein endotoxin reduction was assessed using two temperature-dependent linear fits. Between 170 C and 250 C, calculated D values have been reported from 0.15 min to 3.4 h 16,[18][19][20] (Figure 2). Z values vary depending on testing conditions with reported values of 15 C, 19 30.9 C, 18 46.8 C, 16,19 and 53.7 C 19 being observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations